Modal height and modal flavor: the case of Wolof "di" - Bochnak, M. Ryan; Martinović, Martina (ZAS Papers in Linguistics, 2018)
The Wolof imperfective auxiliary di is compatible with event-in-progress, habitual and future readings. Furthermore, while varieties of all these readings are available for di when it sits in a syntactically low position, only future readings are available when it sits in a syntactically high position. We aim to account for this puzzle by combining several ingredients independently motivated in the literature: (i) event-relative circumstantial modality for event-in-progress, habitual, and a subset of future readings; (ii) metaphyisical modality for generalized future readings; (iii) the idea that syntactic height determines the type of modal anchor that projects a modal base. This study contributes to our understanding of the relation between syntactic height and modal flavor, as well as the nature of modal-aspectual interactions cross-linguistically. Keywords: aspect, future, habitual, imperfective, modality, modal flavor, progressive.